Immune Regulation of Human Embryo Implantation by Circulating Blood Cells - Fujiwara, Hiroshi; Sato, Yukiyasu; Ideta, Atsushi; Aoyagi, Yoshito; Araki, Yoshihiko; Imakawa, Kazuhiko (IntechOpen, 2012)
None